Design of a Communications System for Advanced CubeSat Missions - Phillips, Cameron (Wellington Faculty of Engineering Symposium, 2023)
Advances in miniaturised electric propulsion systems are enabling low-power CubeSats to change orbits mid-mission. CubeSat communications systems must therefore be able to adapt to these changing conditions, ensuring a reliable data link is maintained whilst adhering to the low power budget onboard CubeSats. This report describes a baseline on the performance of the communications system for these potential missions. A high-gain phased planar antenna array operating within the X-band was designed and presented for the proposed missions. A channel model of the 10.475 GHz satellite-Earth link was created and is used to evaluate the performance of PSK and QAM modulation schemes, and error-correcting Turbo Codes. Simulations of the overall performance at varying orbits were used to determine the feasibility of such missions. Results from these simulations demonstrated that a 10.475 GHz communications system using a 4x4 phased planar antenna array, PSK modulation, and turbo coding was capable of maintaining a reliable link throughout the CubeSat’s mission using 1 W of power.